2021
DOI: 10.1080/21663831.2020.1865469
|View full text |Cite
|
Sign up to set email alerts
|

Covalent 2D Cr2Te3 ferromagnet

Abstract: To broaden the scope of van der Waals 2D magnets, we report the synthesis and magnetism of covalent 2D magnetic Cr 2 Te 3 with a thickness down to one-unit-cell. The 2D Cr 2 Te 3 crystals exhibit robust ferromagnetism with a Curie temperature of 180 K, a large perpendicular anisotropy of 7 × 10 5 J m −3 , and a high coercivity of ∼ 4.6 kG at 20 K. First principles calculations further show a transition from canted to collinear ferromagnetism, a transition from perpendicular to in-plane anisotropy, and emergent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Here, we also notice small kinks at low field regions, which may have originated from either thickness inhomogeneity or canted spin orientations of Cr atoms. 34,41 Along the IP direction, the magnetic moment does not show a saturation behavior up to 2 T (not saturated up to 6 T, not shown here). The angle-dependent magnetoresistance (MR) and Hall effect measurements, obtained for the 6.5-nmthick samples at 50 K, confirmed that the magnetic easy axis of the HT C (LT C ) film was aligned along the IP (OOP) direction (see Figure S1 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Here, we also notice small kinks at low field regions, which may have originated from either thickness inhomogeneity or canted spin orientations of Cr atoms. 34,41 Along the IP direction, the magnetic moment does not show a saturation behavior up to 2 T (not saturated up to 6 T, not shown here). The angle-dependent magnetoresistance (MR) and Hall effect measurements, obtained for the 6.5-nmthick samples at 50 K, confirmed that the magnetic easy axis of the HT C (LT C ) film was aligned along the IP (OOP) direction (see Figure S1 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…This suggests that the orbital moment plays an important role in steering the orientation of the spin moment, in turn modulating the MA via spin−orbit coupling.. 48 We also note that spin interactions in Cr−Cr or Cr−Te−Cr schemes are considered as another factor that affects the spin orientations in recent studies of Cr 2 Te 3 . 37,41 Figure 4 shows the cross-sectional scanning transmission electron microscopy (STEM) images of our films, revealing well-stacked layered structures. The bright-field (BF)-STEM images in Figure 4a 50 As LT C film shows interfacial amorphous regions, especially near the lateral boundaries between the domains (white arrows in Figure 4b,e), we believe that a higher Te flux may change the adatom kinetics, which allows the initial formation of the twisted domains followed by different film growth modes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We focused on the construction of 1D MnTe/Cr 2 Te 3 heterostructure, where MnTe shows antiferromagnetic properties and Cr 2 Te 3 is a typical ferromagnet. , MnTe has a hexagonal structure with a P 63/ mmc space group ( a 1 = 4.22 Å, c 1 = 6.73 Å). , This material has recently attracted wide attention due to its strongly antiferromagnetic properties as well as excellent performance in multiple-stable antiferromagnetic memory devices. , Cr 2 Te 3 also possesses a similar hexagonal structure with a P 31 c space group ( a 2 = 6.82 Å, c 2 = 12.08 Å). , This typical ferromagnetic material exhibits a large magnetocrystalline anisotropy ( Ku = 7.9 × 10 5 J m –3 ) and a large coercivity ( H c ≈ 13 kOe). , The similar lattice structures of the two chalcogenides provide a great opportunity to fabricate MnTe/Cr 2 Te 3 heterojunctions with high-quality AFM/FM interface. Figure a shows the side-view crystal structures of MnTe and Cr 2 Te 3 , wherein both Cr and Mn atoms are located in the octahedral interstices of Te atoms.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the construction of 1D MnTe/Cr 2 Te 3 heterostructure, where MnTe shows antiferromagnetic properties and Cr 2 Te 3 is a typical ferromagnet. 29,30 MnTe has a hexagonal structure with a P63/mmc space group (a 1 = 4.22 Å, c 1 = 6.73 Å). 31,32 This material has recently attracted wide attention due to its strongly antiferromagnetic properties as well as excellent performance in multiple-stable antiferromagnetic memory devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation